2015
DOI: 10.4103/2152-7806.158518
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of the intracranial pial arteriovenous fistula

Abstract: Background:Pial arteriovenous fistula (PAVF) is a rare vascular condition comprising of one or more arterial vessels that are in direct communication with the draining veins. The condition is also characterized by the absence of a nidus. Due to high blood flows, varicose systems adjacent to the fistula appear. The key characteristic of the arteriovenous direct transition is that it offers a treatment option in which interruption of the blood flow can occur without removing the entire lesion. This study present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…12 Endovascular interventions are considered less invasive and therefore have emerged as the treatment of choice, especially in lesions with a single feeding artery. 14,15 However, a surgical approach is preferable in complex lesions with multiple arterial feeders and high flow. Goel et al 4 published a series of 14 patients with PAVF successfully treated by surgery without complications or new neurologic deficits.…”
Section: Discussionmentioning
confidence: 99%
“…12 Endovascular interventions are considered less invasive and therefore have emerged as the treatment of choice, especially in lesions with a single feeding artery. 14,15 However, a surgical approach is preferable in complex lesions with multiple arterial feeders and high flow. Goel et al 4 published a series of 14 patients with PAVF successfully treated by surgery without complications or new neurologic deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that PAVF can be successfully treated through closure of the shunt by endovascular [13,14] or surgical means. [15] Unfortunately, the patient chose to leave the hospital and refused further imaging, in spite of the fact that our team strongly emphasized the seriousness of the disease to him.…”
Section: Discussionmentioning
confidence: 99%
“…3 The blood flow of the feeding artery must be reduced in treatment because partial occlusion of the venous varix without the reduction of arterial flow could lead to intraprocedural rupture. 8,37 Treatments for NGPAVF include surgery and endovascular treatment. In areas of easy surgical access, surgeries provide greater benefit.…”
Section: Treatmentsmentioning
confidence: 99%
“…Under long-term increased pressure and high turbulence, drainage veins often exhibit varicosis, the formation of a venous varix, and space-occupying effects. 37,38 For instance, Yang et al reviewed the literature in 2011 and found that varices were present in 77.1% of patients, most commonly in pediatric patients, and that the absence of a varix was significantly correlated with hemorrhage. 39 Even drainage veins have multiple varices.…”
Section: Drainage Veinsmentioning
confidence: 99%
See 1 more Smart Citation